KEANEKARAGAMAN DAN SEBARAN SATWA PRIMATA DI TAMAN HUTAN RAYA SULTAN SYARIF HASYIM KABUPATEN SIAK PROVINSI RIAU Diversity and Distribution Primate Animalsofin Sultan Syarif HasyimForest Park Siak Regency Riau Province - Elfana, Risa; Yoza, Defri; Volcherina, Viny (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Sultan Syarif Hasyim Forest Park is a conservation area with a lowland topography located in Minas District, Siak Regency, Riau Province and has a conservation function. The main function of Tahura SSH is as a nature conservation area that aims to collect flora and fauna, especially primates. Primates are one of the endangered wildlife in nature. One of the efforts that must be done is to conserve animals in their natural habitat in a sustainable manner. This study uses the line transect method by going directly to the field and recording the required data. Data analysis used the formula for estimating density, species diversity, species richness, and primate spatial distribution patterns. Based on data processing obtained 4 primate species consisting of Hylobatidae, namely Cercopithecidae which includes Nokah Lutung (Presbytis femoralis), Long-tailed Monkey (Macaca fascicularis), Beruk (Macaca nemestrina) and Hylobatidae namely Ungko (Hylobates agilis). The SSH Tahura Era has a primate diversity index in the low category with an average of 1.35 and species richness which is also in the low category with a magnitude of 0.85 close to 1.Keywords: Primates, Conservation, Sultan Syarif Hasyim, Forest Park